2006
DOI: 10.1037/0278-7393.32.4.935
|View full text |Cite
|
Sign up to set email alerts
|

When shoes become hammers: Goal-derived categorization training enhances problem-solving performance.

Abstract: Problem-solving theories have not examined how solvers navigate their knowledge to interpret problem situations or to plan strategies toward goals. In this article, the author argues that success in problem solving depends on the solver's ability to construct goal-derived categories, namely categories that are formed ad hoc to serve goals during the instantiation of problem frames. Experiment 1 (N ϭ 140) showed improved problem-solving performance after training to construct goal-derived categories. Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 52 publications
8
71
1
2
Order By: Relevance
“…The insight problems used in this study involved objects such as candles, trucks, watches, ropes, and desk lamps, and I expected university students to have working knowledge of such everyday objects. Prior studies used similar tasks and found university students to be appropriate participants even though students were a convenient population from which to sample (Chrysikou, 2006).…”
Section: Participantsmentioning
confidence: 99%
See 4 more Smart Citations
“…The insight problems used in this study involved objects such as candles, trucks, watches, ropes, and desk lamps, and I expected university students to have working knowledge of such everyday objects. Prior studies used similar tasks and found university students to be appropriate participants even though students were a convenient population from which to sample (Chrysikou, 2006).…”
Section: Participantsmentioning
confidence: 99%
“…The problems used in this study were taken from McCaffrey (2012) and include the Duncker candle problem among others; similar problems have been used in past research on insight generation (e.g., Ansburg & Dominowski, 2000;Chrysikou, 2006;Dominowski & Dallob, 1995 Participants, however, were not obligated to spend the full seven minutes on each question and could move on if they felt that the solution had been found or if they had given up looking for the solution. Participants were also told that they could submit multiple (up to five) textual responses and that they would be given credit if one of their responses was correct 34 I sincerely thank Anthony McCaffrey, who provided not only his dissertation but also the detailed performance statistics for each problem.…”
Section: Task Detailsmentioning
confidence: 99%
See 3 more Smart Citations